The Effect of Growth and Development Stimulation Videos on the Development of Toddlers Aged 6-24 Months - Putri, Hanifa Andisetyana; Prastika, Dewi Andang; Ulfiana, Elisa (Midwifery and Nursing Research, 2024)
Background: Growth is related to the size of physical body structures, while development is an interaction of organ functions such as motor development, language, socialization, and emotions. Stimulation is part of a post-natal environmental factor that is associated with psychosocial factors. From 32 weeks of pregnancy to 2 years of age is the most important stage in the motor development of the child where there is the fastest myelination process in the child's development. The phenomenon that is happening today is that parents lack an understanding of how to perform proper stimulation and have limited knowledge about child development. So there's a need for a medium that can help parents learn how to do the right stimulation so that the child can go through the developmental stages of his or her age.The aim of this study is to find out the impact of video stimulation of growing and development children. Metods: This method of research uses the research type Quasi Experimental Design. The subject of this study is a parent who has a child aged 6-24 months divided into two groups. (control and experiment). Respondents will receive health education related to stimulation of child development by lecture methods (control), and by video media (eksperimen).Results: The discrepancy between pretest and posttest (control and intervention groups), which are unmatched data, was analysed using the Mann-Whitney test. The analysis obtained p=0.219 (p0.05) showed no effect of video stimulation on the growth of children aged 6-24 months. Video media did not give a more significant influence when compared to leaflet media on the control group.Conclusion: There is an effect of growth and development stimulation videos and leaflets on the development of toddlers aged 6-24 months. But there is no significance of the difference between the two tools, namely growth and development stimulation videos and leaflets on the development of toddlers aged 6-24 months.